Quarantine effectiveness during the first and second waves of COVID-19: a cross-sectional and temporal study - Arroyo-Laguna, Juan (2023)
Introduction. The main strategy to face the COVID-19 pandemic was quarantine. Some literature admits its usefulness; on the other hand, other literature emphasizes the harm and risks involved in the application of this measure. Objective. Using weekly and monthly cut-offs of deaths from the first and second waves of COVID-19, the usefulness of quarantine in Peru was evaluated in terms of adherence and effectiveness at the provincial level. Methods. Taking as dependent the number of cases of deaths in each province, the effect of mobility according to different types of places and other covariates on the variable of interest was estimated. Information from the National Center for Epidemiology, Prevention and Disease Control of the Ministry of Health (CDC - MINSA); the National Open Data Platform (PCM - MINSA); data from the National Superintendence of Health (SUSALUD); and aggregate information from Google Analytics were used. A fixed effects model was constructed to estimate effectiveness. Results. In the monthly estimation, during the first and second waves of COVID-19, the covariates and most of the trends in people’s mobility were significant. In the second wave, mobility in parks, supermarkets and pharmacies lost relevance. In the weekly estimation only oxygen availability was not relevant in the second wave; the other independent variables were. Conclusions. The health strategy of quarantine, both in the monthly and weekly estimation, did not have the expected effectiveness, although it achieved adherence.